Using the Capcut Application as A Learning Media - Pahmi, Pahmi; Liping Deng; Marissa Syafwin (Journal International Inspire Education Technology, 2022)
Media helps learn so that the material or information conveyed is more precise and effective, and efficient learning is achieved so that learning objectives are achieved. Media is beneficial as a tool and guide for teachers to describe learning materials systematically to deliver teaching materials more creatively and enthusiastically. In addition, the media helps increase the interest and motivation of students so that students can stimulate and receive material well and quickly understand it. And can increase student creativity so that students are active and promptly digest the learning delivered. Effective learning will require a conducive classroom atmosphere to achieve learning objectives. Using such a method, students only focus on listening to the teacher, quickly feeling bored. By applying the capcut application, teachers can be helped both in explaining the material and by making students not forget to study at home.